2015
DOI: 10.2169/internalmedicine.54.2904
|View full text |Cite
|
Sign up to set email alerts
|

<i>Dialister pneumosintes</i> Bacteremia Caused by Dental Caries and Sinusitis

Abstract: A 62-year-old Japanese woman was hospitalized at the Department of Senology for positive signals on two sets of blood cultures obtained in the Emergency Department. The initial physical examination with enhanced computed tomography of the chest and abdomen did not identify the infectious source. Dialister pneumosintes was identified on 16S rRNA sequencing, and dental caries with sinusitis were subsequently diagnosed based on a dental examination and magnetic resonance imaging. History taking with respect to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…However, there was no evidence of descending transmission of infection from the orthodontic source. In this case, it was a hematogenous spread of infection from the dental abscess, and Dialister pneumosinte s bacteremia of periodontal origin has been documented in the literature [ 5 , 6 ]. A study of 135 systemically healthy dentistry patients revealed D. pneumosintes was the pathogenic organism in 83% of cases of severe periodontitis and 19% of cases of slight periodontitis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no evidence of descending transmission of infection from the orthodontic source. In this case, it was a hematogenous spread of infection from the dental abscess, and Dialister pneumosinte s bacteremia of periodontal origin has been documented in the literature [ 5 , 6 ]. A study of 135 systemically healthy dentistry patients revealed D. pneumosintes was the pathogenic organism in 83% of cases of severe periodontitis and 19% of cases of slight periodontitis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Micro-organisms found and timing of clinical findings strongly suggest that the most likely underlying cause of this vertebral osteomyelitis was the surgical tracheotomy. Namely, the presence in blood cultures of D. pneumosintes, which is a commensal organism exclusively found in the oral cavity, points towards an oro-pharyngeal source [4]. In addition, sepsis and neurologic symptoms occurred 30 days after this procedure, which is consistent with usual timing of vertebral osteomyelitis, a diagnosis often delayed by several months [5].…”
Section: Discussionmentioning
confidence: 83%
“…We isolated it in a 40-year-old immuno-competent female patient with odontogenic CRS. Dialister pneumosintes has already been reported in chronic maxillary sinusitis of odontogenic origin [30,31].…”
Section: Discussionmentioning
confidence: 92%